Brillouin light scattering study of linear and nonlinear spin waves in continuous and patterned magnetic thin films - Liu, Hau-Jian Jason, author; Buchanan, Kristen S., advisor; Gelfand, Martin P., committee member; Kabos, Pavel, committee member; Neilson, James R., committee member (Colorado State University. Libraries, 2014)
This thesis focuses on the use of the Brillouin light scattering (BLS) technique to measure spin waves or magnons in thin films. BLS is an experimental technique that measures the inelastically scattered light from photon-magnon interactions. Broadly, three different experiments are presented in this thesis: the measurements of spin wave properties in iron cobalt (FeCo), yttrium iron garnet (YIG), and microstructures involving Permalloy (Ni80Fe20) and cobalt nickel (CoNi). First, conventional backward scattering BLS was used to measure the spin waves in a set of Fe65Co35 films that were provided by Seagate Technologies. By fitting the spin wave frequencies that were measured as a function of the external magnetic field and film thickness, the quantum mechanical parameter responsible for short range order, known as the exchange parameter, was determined. Second, nonlinear spin waves were measured in YIG using conventional forward scattering BLS with time resolution. Two nonlinear three wave processes were observed, namely, the three magnon splitting and confluence. The nonlinear power threshold, the saturation magnetization, and the film thickness were determined independently using network analyzer measurements. The spin wave group velocities were determined from the space- and time-resolved BLS data and compared to calculations from the dispersion relations. Back calculations showed the location where the three magnon splitting process took place. Lastly, spin waves in Permalloy and CoNi microstrips were measured using a recently developed micro-BLS. The micro-BLS, with a spatial resolution of 250 nm, allows for measuring the effects on the lateral confinement of spin waves in microstrips. The confinement of spin waves led to modifications to the dispersion relations, which were compared against the spin wave frequencies obtained from the micro-BLS. The Permalloy experiments shows non-reciprocity in surface spin wave modes with opposite wavevectors and provides a quantitative measure of the difference in excitation efficiency between the surface spin wave and the backward volume spin wave modes. Measurements were also conducted in the Permalloy microstrips at zero external magnetic field, showing evidence that propagating spin waves can be observed by exploiting the effects of shape anisotropy. Finally, preliminary measurements were done on CoNi microstrips with perpendicular anisotropy. A magnetic signal was detected, however further investigation will be needed to determine the exact origin of the observed signal and to definitively answer the question as to whether or not BLS can be used to measure spin waves in perpendicularly magnetized films. Overall, the experiments and results presented in this thesis show that BLS is a useful tool for measuring spin wave properties in magnetic thin films.
Keywords: Brillouin light scattering; magnetic materials; magnetization dynamics; microstructures; nanoscience; spin waves